Contextualized Mathematics Instruction and Learners’ Problem-Solving Skills at Bantug Elementary School - Padua, Hazel Joy (Azal Arts and Humanities, 2026)
Problem-solving is a central goal of mathematics education, yet many elementary learners struggle to apply mathematical concepts to real-life situations. Contextualized mathematics instruction has been promoted as an instructional approach that connects mathematical content to learners’ everyday experiences, thereby enhancing understanding and problem-solving competence. This study examined how contextualized mathematics instruction influenced learners’ problem-solving skills at Bantug Elementary School. Using a qualitative case study design, data were gathered through classroom observations, semi-structured interviews with mathematics teachers, and focus group discussions with learners. Thematic analysis revealed that contextualized instruction enhanced learners’ problem-solving skills by improving conceptual understanding, increasing engagement with problem situations, and supporting strategic thinking through guided scaffolding. Learners demonstrated greater confidence and persistence when solving word problems grounded in familiar contexts. The findings highlight the importance of intentional contextualization, teacher scaffolding, and instructional leadership support in strengthening mathematics problem-solving at the elementary level.